Dialing up the danger: Virtual reality for the simulation of risk - McIntosh, Verity (Frontiers in Virtual Reality, 2022)
There is a growing interest the use of virtual reality (VR) to simulate unsafe spaces, scenarios, and behaviours. Environments that might be difficult, costly, dangerous, or ethically contentious to achieve in real life can be created in virtual environments designed to give participants a convincing experience of ‘being there’. There is little consensus in the academic community about the impact of simulating risky content in virtual reality, and a scarcity of evidence to support the various hypotheses which range from VR being a safe place to rehearse challenging scenarios to calls for such content creation to be halted for fear of irreversible harm to users. Perspectives split along disciplinary lines, with competing ideas emerging from cultural studies and games studies, from psychology and neuroscience, and with industry reports championing the efficacy of these tools for information retention, time efficiency and cost, with little equivalence in information available regarding impact on the wellbeing of participants. In this study we use thematic analysis and close reading language analysis to investigate the way in which participants in a VR training scenario respond to, encode and relay their own experiences. We find that participants overall demonstrate high levels of ‘perceptual proximity’ to the experience, recounting it as something that happened to them directly and personally. We discuss the impact of particular affordances of VR, as well as a participant’s prior experience on the impact of high-stress simulations. Finally, we consider the ethical mandate for training providers to mitigate the risk of traumatizing or re-traumatizing participants when creating high-risk virtual scenarios.